Lifestyle factors associated with age-related macular degeneration: Case-control study - Kráľová, Jana Šalková; Kolář, Petr; Kapounová, Zlata; Veselý, Petr; Brázdová, Zuzana Derflerová (European journal of ophthalmology, 2024)
BACKGROUND: Age-related macular degeneration (AMD) is one of the major causes of vision loss in individuals aged ≥ 65 years in developed countries. This study aimed to determine the associations between modifiable risk factors and AMD. This is the first study describing the relationship between lifestyle factors and AMD in the Czech Republic. METHODS: In this cross-sectional case-control study, 93 AMD cases and 58 controls without AMD and cataract were included. All participants were examined by Optical coherence tomography at the Clinic of Eye Treatment at the University Hospital Brno. Data were collected using a pre-tested self-report questionnaire in a face-to-face interview. RESULTS: We found significant associations between those who were living in the city (OR 95% CI: 2.19 (1.0-4.6); p = 0,039), with a positive family history of AMD (OR 95% CI: 12.75 (1.6-98.6); p = 0,015), exposure to cigarette smoke (OR 95% CI: 2.72 (1.4-5.4); p = 0,004), and daily exposure to passive smoking (OR 95% CI: 2.29 (1.0-5.1); p = 0,045) and AMD. In men, we found significant associations between daily sunlight exposure (OR 95% CI: 2.98 (1.0-8.5); p = 0,041), short or long sleep duration (OR 95% CI: 3.98 (1.2-13.2); p = 0,024) and AMD. Men daily exposed to sunlight were at a 2.98 times higher risk of AMD than men with less than daily sunlight exposure. Men with short or long sleep duration (< 6 and > 8 h) were at a 3.98 times higher risk of AMD than men with recommended sleep duration of 6-8 h. CONCLUSIONS: An increased risk of AMD was observed for living in the city, family history of AMD, exposure to cigarette smoke, and daily exposure to passive smoking. Increased risk of AMD was observed for daily sunlight exposure and short or long sleep duration; however, only in men.
Keywords: optická koherentní tomografie; Cross-Sectional Studies; Male; Risk Factors; Macular Degeneration; Česká republika; Aged; Case-Control Studies; Life Style; mužské pohlaví; senioři; průzkumy a dotazníky; Smoking; znečištění tabákovým kouřem; Czech Republic; Tobacco Smoke Pollution; senioři nad 80 let; životní styl; lidé; ženské pohlaví; studie případů a kontrol; Humans; makulární degenerace; rizikové faktory; průřezové studie; Tomography, Optical Coherence; Aged, 80 and over; Female; Surveys and Questionnaires; lidé středního věku; kouření; Middle Aged